You are on page 1of 4

# ECE 101 – Linear Systems, Fall 2018

October 2, 2018

## Then z1 through z5 are:

q
(a) z1 = x0 − jy0 (b) z2 = x20 + y02
(c) z3 = −x0 − jy0 = −z0 (d) z4 = −x0 + jy0
(e) z5 = x0 + jy0 = z0 (recall, ejθ is periodic with period 2π)

Plots:

1
1.49 Once in polar form rejθ , the magnitude is given by r and angle given by θ.

(a) 2ejπ/3 (b) 5ejπ (c) 5√ 2ej5π/4
jtan−1 (4/3) j53.13o
(d) 5e
√ −j5π/12 = 5e (e) 8e−jπ (f) 4 2ej5π/4
(g) 2 2e (h) e−j2π/3 (i) ejπ/6

Plot:

## (a) Summing (i) + (ii) yields cos θ = 21 (ejθ + e−jθ ).

(b) Subtracting (i) - (ii) yields sin θ = 2j1 (ejθ − e−jθ ).
(e) From Euler’s relation: ej(θ+φ) = cos(θ + φ) + j sin(θ + φ). We can also write
ej(θ+φ) = ejθ ejφ
= (cos θ + j sin θ) (cos φ + j sin φ)
= (cos θ cos φ − sin θ sin φ) + j (sin θ cos φ + cos θ sin φ) .
Equating the real and imaginary parts of these two representations of ej(θ+φ) gives us the
“sum identities”:
cos(θ + φ) = cos θ cos φ − sin θ sin φ
sin(θ + φ) = sin θ cos φ + cos θ sin φ.

2
1.52 (c) z + z ∗ = x + jy + x − jy = 2x = 2Re {z}

## (d) z − z ∗ = x + jy − x + jy = 2jy = 2jIm {z}

1.53 (a) (ez )∗ = (ex+jy )∗ = (ex ejy )∗ = ex e−jy = ex−jy = ez

(c) |z| = rejθ = |r| = re−jθ = |z ∗ | In words, taking the conjugate means flipping across

the real axis; this negates the angle, but does not affect the magnitude.

(d) |z1 z2 | = r1 r2 ej(θ1 +θ2 ) = |r1 r2 | = |r1 | |r2 | = |z1 | |z2 |

PN −1 PN −1
n=0 αn = n=0 1=N

## For α 6= 1, if we multiply the sum by (1 − α), we obtain:

PN −1 PN −1 PN −1
(1 − α) n=0 αn = n=0 αn − n=0 αn+1 = 1 − αN

since the α1 through αN −1 terms cancel out. Dividing both sides by (1 − α), we obtain the
desired result:
N −1
1 − αN
αn =
X

n=0 1−α
(b) Since |a| < 1, we know that

lim αN = 0.
N →∞

## Referring to part (a), we

∞ N −1 N −1
1 − αN 1
αn = lim αn = lim
X X X
= .
n=0
N →∞
n=0
N →∞
n=0 1−α 1−α

(c) Since |a| < 1, the identity in part (b) holds. We differentiate both sides of part (b) with

respect to α to get

!
d X d 1
 
n
α = .
dα n=0 dα 1 − α
Evaluating the derivatives, we get

1
nαn−1 =
X
.
n=0 (1 − α)2
So,

α
nαn =
X
.
n=0 (1 − α)2

3
(d) Again, since |a| < 1, the identity in part (b) holds. We use it to rewrite and evaluate

## the given summation as

∞ ∞
αk
αn = αk αn =
X X
.
n=k n=0 1−α
P9 1−ejπ10/2
1.55 (a) n=0 ejπn/2 = 1−ejπ/2
=1+j

P7 P9
(b) n=−2 ejπn/2 = m=0 ejπ(m−2)/2 , using the substitution m = n+2 ⇒ n = m−2. Then,

P9
= e−j2π/2 m=0 ejπm/2 = e−j2π/2 (1 + j) = −(1 + j).

## (c) Here, use the result from Problem 1.54(b):

P∞ 1 n jπn/2 1
n=0 2 e = 1− 12 ejπ/2
= 0.8 + 0.4j

## 1 n jπn/2 1 2 j2π/2 1 m jπm/2

(d) ∞
P∞
using the substitution m = n–2 ⇒ n = m+2.
P
n=2 2
e = 2
e m=0 2 e ,
Then,

P∞ 1 m jπm/2
= (0.25)(−1) m=0 2 e = (−0.25)(0.8 + 0.4j) = −0.2 − 0.1j

## (e) Using the identity we proved in 1.51(a), we have

P9 P9 P9
n=0 cos(πn/2) = 1
2 n=0 ejπn/2 + 1
2 n=0 e−jπn/2 = 12 (1 + j) + 12 (1 − j) = 1

R 8 jπt/2 1 2
1.56 (c) 2 e dt = jπ/2
ejπt/2 |82 = jπ (ej4π − ejπ ) = − π4 j

## (f) Using the identity from 1.51(b),

R ∞ −2t R ∞ h e−(2−3j)t −e−(2+3j)t i 1/2j 1/2j 3
e sin(3t)dt
0 = 0 2j
dt = 2−3j
− 2+3j
= 13